Une nouvelle subjectivité féminine en Iran - Khosrokhavar, Farhad (Esprit, 2023)
Les jeunes générations, notamment de femmes, rejettent un régime théocratique macabre au nom de la joie de vivre et de la liberté.
Keywords: 2000 à aujourd'hui; 2020-2029; approches et analyses; asie; com5170; cours; discipline; droits des femmes*; féminisme islamique; histoire et politique; iran; militance; patriarcat; premier cycle; périodes historiques; régions géographiques; résistance; sciences humaines; sociologie; systèmes d'oppressions; thématiques

Class S: appropriation of ‘lesbian’ subculture in modern Japanese literature and New Wave cinema - Shamoon, Deborah (Cultural Studies, 2021)
In the 1920s in Japan, girls attending single-sex secondary schools developed a girls’ culture (shōjo bunka) or subculture to insulate themselves temporarily from the pressures of patriarchal society. Part of this subculture was a practice called s kankei (s or sister relationships), also called Class S, which were same-sex romantic attachments between classmates, condoned at the time as a temporary practice relationship that would end upon graduation, followed by an arranged marriage. Although s relationships were not ‘lesbian’ in the contemporary sense, literature and film created by men in the 1920s through the 1960s appropriated aspects of girls’ culture, including exploitative representation of female homosexuality. One example is Manji (Quicksand, 1928) by Tanizaki Jun’ichirō, which depicts an s relationship as lurid and perverse. Kawabata Yasunari plagiarized from his female disciple Nakazato Tsuneko in order to publish the most popular Class S novel of the era, Otome no minato (Harbor of Girls, 1937). Kawabata also included exploitative scenes of female homosexuality in his novel Utsukushisa to kanashimi to (Beauty and Sadness, 1963). Both Tanizaki’s and Kawabata’s novels were made into films by New Wave directors, Manji in 1964 by Masumura Yasuzō and Beauty and Sadness in 1965 by Shinoda Masahiro, and featured the first depictions of ‘lesbianism’ in Japanese film. Although these films reinscribe the male gaze, they helped inspire a nascent gay culture and opened the way for more authentic gay cinema. This essay recenters girls’ culture in modern Japanese literature and film, and discusses the variable meaning of female homosexuality for different audiences.
Keywords: approches et analyses; arts; asie; discipline; discours dominant; japon; patriarcat; personnes lesbiennes; ressource en ligne; régions géographiques; systèmes d'oppressions; études culturelles; études littéraires

Bargaining with confucian patriarchy: Money, culture, and gender division of labor in Taiwanese immigrant families - Gu, Chien-Juh (Qualitative Sociology, 2019)
Previous studies of immigrant families have reported consistent findings concerning the positive effects of employed wives’ financial contributions and Western gender ideologies on women’s bargaining power in the family. This paper revisits this thesis. Data presented in this article are derived from a larger project based on 45 life-history interviews with Taiwanese immigrant women in a Midwest urban region. Findings suggest that women’s employment does not serve as a key factor that shapes spousal power relations in Taiwanese immigrant families. Rather, gendered work-family boundaries and individuals’ abilities construct main rationales in women’s interpretations of their division of labor at home and their dominance in financial management. None of the women interviewed consider Western culture as an inspiration for egalitarian gender ideology. In contrast, Confucian culture is often used by husbands and mothers-in-law to demand traditional gender practice, which is further reinforced and surveilled by the Taiwanese ethnic community. Therefore, the interconnections of work, family, money, culture, and power and their interactive effects on spousal relations are more complicated than previously suggested. This study also reveals varied forms of patriarchal bargaining in Taiwanese immigrant families. Married women tend to accommodate patriarchy in their housework assignment, but actively bargain in their management of family finances and persistence to seek employment. The findings suggest that heterogeneity within the research sample, household structure, and individuals’ subjectivities must be examined to understand the nuances and complexity of women’s gender strategies and bargaining power in immigration families. Theoretical implications of the study are also discussed.
Keywords: amériques; approches et analyses; asie; discipline; famille; femmes* immigrantes; patriarcat; projet charge mentale; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; taiwan; thématiques; travail; travail domestique; états-unis

Racializing heterosexuality: Non-normativity and East Asian characters in James Bond films - Hiramoto, Mie; Pua, Phoebe (Language in Society, 2019)
This article investigates how naturalized models of hegemonic masculinity affect race and sexuality in the James Bond film series. Through close analysis of film dialogue and paralinguistic cues, the article examines how the sexualities of East Asian female and male characters are constructed as oversexed and undersexed, respectively. The analysis therefore affirms Connell's (1995) conception of white heterosexual masculinity as exemplary: East Asian characters are positioned not only as racial Others, but as bodies upon which Bond's heterosexual masculinity is reflected and affirmed as normative and, by extension, ideal. In this way, race is curiously invoked to ‘explain’ sexuality, and Bond's unmarked white masculinity becomes the normative referent for expressions of heterosexual desire. By showing how the sexuality of East Asian characters is typecast as non-normative, the article gestures toward the possibility of theorizing racialized performances of heterosexuality as queer.
Disponible en ligne à https://www-cambridge-org.proxy.bibliotheques.uqam.ca/core/journals/language-in-society/article/racializing-heterosexuality-nonnormativity-and-east-asian-characters-in-james-bond-films/52C50BE7F19552D50389CDED9913BCE3
Keywords: approches et analyses; arts; arts visuels et médiatiques; asie; asie de l'est; cinéma; cours; discipline; identités de genre; intersectionnalité; lin2685; patriarcat; pol5480; premier cycle; privilèges; racisme; ressource en ligne; régions géographiques; systèmes d'oppressions; études de genres

Invisible labor and women’s double binds: Collusive femininity and masculine drinking in Russia - Utrata, Jennifer (Gender and Society, 2019)
The heavy drinking of alcohol remains primarily a hegemonically masculine ritual worldwide. Yet scholarship has undertheorized women’s practices in shaping the boundaries of masculine rituals, including drinking. Drawing on 12 months of ethnographic fieldwork and 151 interviews with single mothers, married mothers, nonresident fathers, and grandmothers from diverse class backgrounds, I demonstrate that Russian women perform extensive invisible management labor in attempting to produce responsible men. Constrained by a starkly unequal gender division of domestic labor, wives and mothers engage in varied “patriarchal bargains” as they shape men’s drinking practices, co-producing hegemonic masculinity. Whereas in the Soviet period women also managed men’s drinking, today new gender strategies have emerged. More women are held accountable to a collusive femininity involving both accommodation and resistance, upholding men’s drinking privileges only if breadwinning occurs. As women perform invisible labor, they end up reproducing the conditions that demand this labor from them in the first place. Some women embrace an alternative femininity by becoming single mothers and refusing to manage men’s drinking, especially when men fail as breadwinners. Theorizing collusive and alternative femininities, as well as women’s invisible labor, advances our knowledge of how multiple femininities shape, and may in time change, hegemonic masculinity. © 2019 by The Author(s).
Keywords: approches et analyses; asie; consommation d'alcool; discipline; hégémonie masculine; patriarcat; projet charge mentale; russie; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; travail invisible

Féminicides en Inde : un continuum de violence contre les femmes - Messier, Geneviève (Université du Québec à Montréal, 2018)
Ce travail de recherche dirigé s'intéresse aux différentes manifestations de la violence faite aux femmes en Inde, particulièrement à la violence mortelle envers les femmes. Il s'agit de démontrer l'existence d'éléments de continuité entre trois types de violence différents, c'est-à-dire les foeticides, ou avortements sélectifs des foetus de sexe féminin, les violences sexuelles et mortelles contre les femmes dans l'espace public ainsi que les violences contre les femmes dans les zones de conflit du territoire indien. L'analyse de chacune de ces manifestations de violence a été faite par le biais d'éléments de définition du concept de féminicide. Trois aspects de la définition de féminicide présentée dans ce travail ont été systématiquement analysés pour les trois types de violence identifiés. Chacun de ces types de violence se déroule dans le cadre de rapports sociaux de sexe inégaux, dans une situation d'impunité créée par le gouvernement indien et le concept d'intersectionnalité a permis de démontrer que les éléments identitaires des femmes indiennes autres que le genre jouent un rôle prépondérant pour expliquer la violence dont elles sont victimes. Cette analyse nous a permis de démontrer l'existence d'un continuum de la violence contre les femmes en Inde. Ce continuum s'étend de la sphère privée à la sphère publique et concerne le niveau local tout comme l'arène internationale. De plus, ce travail a aussi permis de démontrer la pertinence du concept de féminicide à l'extérieur du contexte latinoaméricain dont il est issu. Les résultats de ce travail se trouvent limités par le fait que seulement trois types de violence ont pu être analysés et que certains types de violences spécifiques au contexte indien, comme les épouses brûlées vives (bride burning) et les meurtres pour la dot, n'ont pas pu être intégrés à l'analyse. ___________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : féminicide, continuum de la violence, Inde, violence faite aux femmes
Keywords: IREF; approches et analyses; asie; discipline; inde; mémoires/thèses; patriarcat; ressource en ligne; régions géographiques; science politique; science politique et droit; systèmes d'oppressions; thématiques; violences

Visual representation of gender in flood coverage of Pakistani print media - Ali, Zarqa S. (Weather and Climate Extremes, 2014)
This paper studies gender representation in the visual coverage of the 2010 floods in Pakistan. The data were collected from flood visuals published in the most circulated mainstream English newspapers in Pakistan, Dawn and The News. This study analyses how gender has been framed in the flood visuals. It is argued that visual representation of gender reinforces the gender stereotypes and cultural norms of Pakistani society. The gender-oriented flood coverage in both newspapers frequently seemed to take a reductionist approach while confining the representation of women to gender, and gender-specific roles. Though the gender-sensitive coverage displayed has been typical, showing women as helpless victims of flood, it has aroused sentiments of sympathy among readers and donors, inspiring them to give immediate moral and material help to the affected people. This agenda set by media might be to exploit the politics of sympathy but it has the effect of endorsing gender stereotypes.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; cinéma; communication; discipline; environnement; inondations; médias; pakistan; patriarcat; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; stéréotypes de genre; systèmes d'oppressions; thématiques

Le sexe du militantisme - Fillieule, Olivier; Roux, Patricia (Presses de Sciences Po, 2009)
Le sexe du militantisme propose une analyse de la (re)production des rapports de pouvoir au travers des pratiques militantes, saisissant les logiques par lesquelles les inégalités de genre, de classe et de race imprègnent le militantisme, qu'il soit de gauche ou de droite, progressiste ou conservateur. Premier ouvrage en français à explorer le militantisme dans une perspective de genre à partir de recherches empiriques sur les partis, les syndicats et les mouvements sociaux, il rassemble des politistes, sociologues, anthropologues et historiennes dont le souci est de ne pas appréhender les luttes politiques comme si elles étaient « neutres » et non sexuées. Une contribution majeure à l'étude des mobilisations collectives qui complète les analyses classiques, aveugles aux rapports de genre.
Keywords: LGBTQIA2+; amérique du nord; amérique latine; amériques; anarchisme; anthropologie; approches et analyses; asie; canada; caraïbes; discipline; europe; france; genre; guyane française; histoire; hétérosexisme; identités LGBTQIA2+; inégalités; israël; italie; militance; mouvements sociaux; patriarcat; québec; racisme; rapports sociaux; rapports sociaux de sexe; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; syndicat; système colonial; systèmes d'oppressions; thématiques; violences

Rocking Sexualities: Iranian Migrants' Views on Sexuality - Ahmadi, Nader (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2003)
The purpose of this article is to put forward a theoretical discussion about Islamic views of sexuality and by means of an example show how Iranian immigrants in Sweden view sexuality and sexual culture. Building on theories that compare individualistic and holistic ways of thinking, the article seeks to elucidate the impact of basic cultural qualities on the formation of sexualities. The conclusion of the article is that the encounter with the Swedish way of thinking and the Swedish sexual culture seems to have influenced Iranian migrants' views on the nature of the relationship between couples and sexual decision making within the relationship. Exposed to an individualistic ideology and lifestyle in Sweden, Iranian migrants show a clear tendency to revise their previous holistic way of thinking, especially in regard to sexuality: the traditional, authoritarian, patriarchal sexual relationship among Iranian migrants in Sweden is giving way to more egalitarian relationships, and a relatively strong tendency towards a similarity of views between the sexes regarding sexuality can be observed. The most important change that could be observed in regard to the respondents in the study is probably an increased individualism.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; asie; cours; discipline; europe; inégalités; iran; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexualité; suède; systèmes d'oppressions; thématiques; travail social

Territoires en mouvement : femmes et danses de résistance en Arménie - Institut de recherches et d'études féministes
Et si danser devenait un acte de résistance, un territoire à soi quand tout disparaît ? Dans cet épisode, nous partons en Arménie avec Sona Pogossian, où la danse devient un pilier identitaire face à l’enclavement, à la perte de terres, et aux blessures de l’histoire. La danse, architecture vivante et mouvante, est un territoire immatériel que l’on porte en soi. Les femmes y incarnent un double pilier : celui de la mère et celui de la nation. Dans une société où la femme est le noyau de l’identité nationale, comme dans bien d’autres luttes pour l’autodétermination, la figure maternelle devient le symbole d’un « NOUS » collectif, profond et résistant. Biographie : Artiste de la scène, Sona a suivi de multiples formations en anthropologie et pratiques des arts scéniques, dont au sein du conservatoire de Lyon, de l’université d’État de Moscou d’Art et de Culture, de l’université Paris 8, entre autres. Son parcours pluriel l’amène aujourd’hui à réaliser un doctorat (thèse-création) à l’UQAM en études et pratiques des arts, où elle tente de mettre en lumière les corporalités des femmes en phénomène de guerre. Enregistré durant la Tournée des cégeps à l’automne 2024 (https://iref.uqam.ca/babillard/tournee-des-cegeps-foire-feministe-feministes-dans-la-cite/)par Juliette Chevet et Rajae Anys. Écrit et monté par Rajae Anys. Avec le soutien financier du CRSH.
Keywords: 2000 à aujourd'hui; 2020-2029; Arménie; arts; asie; danse; discipline; doits des femmes; foire féministe; guerre; maternité; militance; musique; patriarcat; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques